The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1136/bjo.73.4.283
|View full text |Cite
|
Sign up to set email alerts
|

Ptosis following cataract and trabeculectomy surgery.

Abstract: SUMMARY A prospective study was carried out to estimate the incidence and severity of ptosis following cataract extraction and trabeculectomy. A postoperative ptosis of 2 mm or more was found in 6*2% of all cases. In this series the incidence of ptosis following surgery under local anaesthesia was greater than that under general anaesthesia. The aetiology and management of this complication are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
1
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 12 publications
(2 reference statements)
0
22
1
1
Order By: Relevance
“…14,15 Other studies have supported this assertion with their findings that older subsets of patients did not have an increased incidence of ptosis compared with younger subsets. 8,15 In addition, despite speculation that various factors associated with surgery precipitate ptosis in patients with a preexisting aponeurotic defect, 4,16 preexisting ptosis or prior ocular surgery do not seem to predispose patients to further postoperative ptosis. 7 However, ptosis was more common in eyes with ptosis in the fellow eye in the study by Feibel et al 13 Preoperative lid crease, sulcus appearance, lash rotation, and levator function do not seem to have any predictive value for subsequent ptosis, 7,13 but smaller preoperative palpebral fissure measurements have been associated with higher incidence of postoperative ptosis.…”
Section: Ptosis After Cataract Surgerymentioning
confidence: 93%
“…14,15 Other studies have supported this assertion with their findings that older subsets of patients did not have an increased incidence of ptosis compared with younger subsets. 8,15 In addition, despite speculation that various factors associated with surgery precipitate ptosis in patients with a preexisting aponeurotic defect, 4,16 preexisting ptosis or prior ocular surgery do not seem to predispose patients to further postoperative ptosis. 7 However, ptosis was more common in eyes with ptosis in the fellow eye in the study by Feibel et al 13 Preoperative lid crease, sulcus appearance, lash rotation, and levator function do not seem to have any predictive value for subsequent ptosis, 7,13 but smaller preoperative palpebral fissure measurements have been associated with higher incidence of postoperative ptosis.…”
Section: Ptosis After Cataract Surgerymentioning
confidence: 93%
“…Lower incidences of postoperative ptosis have been reported after general anaesthesia, compared with local anaesthesia. 12,13 One reason may be that under general anaesthesia muscle relaxants prevent patients from squeezing against a rigid speculum, whereas they are not prevented from doing this under local anaesthesia.…”
Section: Resultsmentioning
confidence: 99%
“…Most subsequent studies use their criteria to define postoperative ptosis, although its incidence varies widely. Studies have reported rates between 0 and 44% with different surgical and anesthetic techniques, although most seem to fall between 6 and 12% (Table 1) [6][7][8][9][10].…”
Section: Ptosis Following Cataract Surgerymentioning
confidence: 99%
“…They include ptosis in the nonoperative eye and a narrow palpebral aperture in the operative eye [6,9]. Conversely, patient age, sex, LPS function, eyelid crease position, dermatochalasis, and preoperative ptosis in the operative eye have no effect on rates of postoperative ptosis [6,7,9,11].…”
Section: Ptosis Following Cataract Surgerymentioning
confidence: 99%